Physical, chemical and biological characterization as support for water governance in a hydrogeological system of Colombia (2018)
ABSTRACT: Understanding the physical, chemical and biological system is an indispensable precondition to addressing groundwater management. This understanding is based on Conceptual Hydrogeological Models, which contain different interpretations and their validity is checked through the application of specific research techniques (numerical modelling, hydrochemistry, isotope hydrology, process evaluation and biological functions). This paper describes the experience carried out by an academic team that, together with entities responsible for the protection of water resources, established strategic alliances to improve the knowledge of the hydrogeological system, providing new elements for governance. This study was carried out in the Urabá antioqueño zone, located north-west of Colombia. A complex aquifer system is located in the region, characterized by a series of permeable, semi-permeable and impermeable layers. In such a layered aquifer the determination of the physical, chemical and biological characteristics of the layers and their management are a challenge for researchers because groundwater represents a strategic resource for supplying the population and developing economic activities. Starting from the conceptual hydrogeological model, multiscale numerical modelling exercises have been carried out, enabling the characterization of local, intermediate and regional flow systems. In addition, by determining the natural background level, the concentration ranges of chemical compounds from natural sources were obtained, in order to detect future changes in water quality. It was also possible to examine the stygofauna, which allowed the recognition of different types of organisms (stygobits, stygophiles and stygoxens) associated with underground ecosystems. These scientific elements serve as a support for the management instruments such as the groundwater management plan that is important for water governance, ensuring its future sustainability.